(3GdTGeds - (3CHh GdbGSe ESeGYjd Hf GdMSf Hf Ydj GdHjgbj,J (B402 (3g` s
(3ChdgG (B:s
(3Chd GdcJGH s
(3BNQgG (B:s
(3cJGH GdbSeg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B312 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B264s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B9 - (3U (B261 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1024s
Keywords: (3Gdabg GdMfajs